The Concept of Hadith Maudhu and Its Contextualization in Information Management in the Digital Era - Fajar Rachmadhani (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
The purpose of this research is to discuss the role of ulumul hadith studies in responding to contemporary problems, specifically to discuss the concept of hadith maudh?, as well as its relevance and contextualization in helping and responding to news or information in the digital era, especially in dealing with hoaxes, where there are similarities of motives, indicators, and solutions to eradicate them. The results of this research are expected to be useful and contribute both practically and theoretically. The practical benefits of this research are expected to be able to provide encouragement and motivation to Muslims to always study vast treasures (khazanah) of Islamic science, especially in the ulumul hadith studies, so that a moderate Islamic society is realized and always prioritizes caution and clarification in accepting and disseminating news and information in this digital era. The type of this research included qualitative research, and its primary sources were the principles ulumul hadith books which discussed about hadith maudh?. Additionally, its secondary sources were the information contained in journals, websites, and others. This research used content analysis approach. This method was used to conclude efforts to bring up the characteristics of messages carried out objectively and systematically